THE MODERN CONDITION OF THE FINANCIAL MARKET OF KAZAKHSTAN - A.A. Ussipbekov; A.B. Alibekova; B.B. Doskalieva; A.B. Alibekova (Academic Journal of Physical and Chemical Sciences, 2019)
The various segments of the financial market are closely interconnected, which is economically manifested and justified by the movement of financial flows and the desire to equalize the profitability of financial instruments of different segments. Analysis of financial indicators of the financial market, as a rule, is carried out from the position of a particular segment. The article analyzes the financial condition of the banking sector of Kazakhstan, as one of the segments of the financial market.